Komparasi Sistem Perpajakan pada Masa Abu Ubaid dengan Sistem Perpajakan di Indonesia - Ilma Sari, Reni (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This article aims to find out the comparison of the tax system during the Abu Ubaid period with the tax system in Indonesia. Abu Ubaid firmly believes that the principle of justice in the economy is very important to achieve economic and social welfare. Therefore, Abu 'Ubaid's Kitab al Amwal is an economic masterpiece that addresses pressing issues in the fields of law, politics, and international relations. The Islamic public financial system, especially with regard to government administration, is explained in great detail in Al-Amwal. Since taxes are a major source of revenue for the government, any reform must be carried out in a method with clear goals and benchmarks. Tax reform must also pay attention to the sustainability of the economy both domestically and internationally, the ease of implementation, and the efficiency of the resulting payments. The tax reforms of 1983, 1994 and 1997 were widely successful and widely criticized by politicians. In keeping with the reformist spirit, the government does not need to tighten its grip on power. The government has identified the Head of the Ministry of Finance's Budget Analysis Section as an appropriate point of contact for questions about how Indonesia's tax strategy is being implemented. Keywords: Comparison, Taxation during the Abu Ubaid period, Indonesian Taxation.